Working for It: The Other Work in Graduate School, Procuring Fellowship Funding & Designing the Research to Accompany the Funds - Dominique T. Chlup; Lisa Gardner Flores; Joellen Coryell (Adult Education Research Conference, 2006)
Two current fellows at a state literacy center with University affiliations and a former doctoral fellow at a national center will discuss their experiences procuring a major fellowship to help pay for their graduate studies. How these fellowships allowed them to participate in the design and implementation of research are also discussed.
Keywords: Fellowship funding; proposal writing; financial suppor